A Comparison of Models of Parole Outcome - Gould, Larry Allen (1991)
The focus of this dissertation is on the criteria which parole boards use as the basis for their decision to release an offender on to parole. The literature strongly suggests that there are some objective measures of dangerousness on parole, such as the Salient Factor Score; however, the literature also indicates that parole boards use a great deal of subjective evaluation in making their decisions. Many of the subjective concepts used by parole boards can be measured objectively through a grounding in criminological theory. A model of parole outcome prediction which measures objectively several of the previously subjective variables, including association and the elements of the social bond, was developed. These additional variables are added to the Salient Factor Score instrument to test the predictive ability of a new parole risk model. To test the addition of the new variables a sample of offenders who were incarcerated and then released on parole was used. The results indicate that the predictive power of the new model is significantly greater than that of the old model. Additionally, the effectiveness of the inclusion of the new variables suggests that theoretical criminology can be useful in practical situations